Cites and Domestic Economy in Indonesia: The Efforts of the Indonesian Government to Change The Lamakera Fishers’ Commodity in Implementing the 2013 CITES Convention - Septiyana, Iyan (Journal of Indonesian Social Sciences and Humanities, 2017)
In 2012 researchers proposed a moratorium on international trade in the import and sale of the gills of Manta Rays. In the 2013 CITES conference in Bangkok, a convention to prohibit manta ray and shark hunting is agreed by 93 countries. Indonesia as the second sea fish producer affected by this policy, especially for the fishers in Lamakera, Solor Islands, East Nusa Tenggara. Since hundreds of years ago, the Lamakera fishers known as stingray and whale hunter, and stingrays species is their main economic commodity. Indonesia, as a part of CITES, is bound and must obey to the convention. Then, in 2014, the Indonesian government has issued a regulation banning manta rays. This paper will use the liberal institutional approach in describing how the Indonesian government tackles the issue of environment, implementing CITES conventions, and solve the economic problems of local people that involving diverse stakeholders.